The Determinants of Export Decisions and Attitudes to a Distant Market: Norwegian Fishery Exports to Japan - Gripsrud, Geir (Journal of International Business Studies, 1990)
This paper focuses on the process that occurs when active exporters, reacting to new opportunities, either enter or increase exports to psychologically distant markets. The overall purpose of the study is to provide guidance for export promotion activities. Since future exports cannot be observed directly, the attitude regarding future exports is introduced as this study's primary dependent variable. A model is formulated where firm and product attributes, as well as perceived barriers/opportunities are proposed as determinants of attitudes towards future exports. Previous export experience in the relevant market is also introduced as an additional variable in explaining attitude towards future exports. The model is tested in a two-step procedure with multiple discriminant and regression analysis. The data used to test the model is taken from a survey of Norwegian exporters of fishery products.